2004
DOI: 10.1111/j.1365-2222.2004.01969.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients with seasonal allergic rhinitis and concomitant asthma

Abstract: Patients with seasonal allergic rhinitis and concomitant asthma appear to differ from those with persistent asthma. A prospective study should be designed to discover whether patients with seasonal rhinitis and asthma may represent a distinct nosological entity, 'allergic airway disease'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 32 publications
6
25
0
Order By: Relevance
“…Pollen-allergic patients commonly have rhinitis and conjunctivitis during the pollen season. They can also have pharyngitis, cough and wheezing (1940). In most patients, chest symptoms are not associated with a measurable airflow obstruction (1940)(1941)(1942).…”
Section: Common Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pollen-allergic patients commonly have rhinitis and conjunctivitis during the pollen season. They can also have pharyngitis, cough and wheezing (1940). In most patients, chest symptoms are not associated with a measurable airflow obstruction (1940)(1941)(1942).…”
Section: Common Risk Factorsmentioning
confidence: 99%
“…They can also have pharyngitis, cough and wheezing (1940). In most patients, chest symptoms are not associated with a measurable airflow obstruction (1940)(1941)(1942). Moreover, true asthma exacerbations may occur during dry days in some patients naturally exposed to pollens (1943,1944), probably because pollen allergens can be born by submicronic particles which can penetrate deeply into the airways (399).…”
Section: Common Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence that chronic allergen exposure caused by house dust mites (69) or pollens (70) can have the same effect is weaker possibly because chest symptoms in asthma may also be related to nasal symptoms (71). In experimental studies with asthmatic patients, a single, high-dose allergen challenge can easily reproduce most, if not all, features of an asthma exacerbation (72).…”
Section: Acute and Chronic Allergen Exposurementioning
confidence: 99%
“…Studies indicate a strong relationship between asthma and AR [7][8][9], with ,20-50% patients with AR experiencing concomitant asthma [10]. A 23-yr follow-up study of college students in the USA showed that AR occurred in 86% of asthmatics [11], whereas a French study [12] that assessed the QoL in patients with AR and asthma found that 78% of asthmatics also suffered from AR.…”
mentioning
confidence: 99%